Examining the Relationship Between Rental Housing Assistance Type and Characteristics of Neighbourhood Satisfaction in Canada - Simard, Laurence; Leloup, Xavier; Leviten-Reid, Catherine; Desjarlais-deKlerk, Kristen; Muhajarine, Nazeem; Mendez, Pablo (Canadian Journal of Regional Science / Revue canadienne des sciences régionales, 2026)
This paper analyzes the Canada Housing Survey (CHS) first-wave data (2018) to examine the relationship between various aspects of neighbourhood satisfaction and rental housing type (e.g., government, co-operative, not-for-profit [NFP], and private) inherited from past Canadian housing policies. Using partial proportional odds models, we consider feeling of safety, resource accessibility, and community/neighbourhood satisfaction. This approach allows for nuanced interpretations beyond purely objective measures, encompassing factors like service adequacy, personal characteristics, and neighbourhood issues. CHS data reveal lower neighbourhood satisfaction among renters, with public housing showing lower satisfaction and lower feelings of safety compared to other housing types. Co-operative and NFP housing appear to offer less favourable options for tenants occupying a subsidized unit in terms of access to services responding to their needs. Finally, a predominance of personal characteristics appeared in the modelling, which we believe demonstrates persistent inequality in Canada linked with urban design and housing access for historically marginalized groups.